MEDICINAL HERBS AND PHYTOCHEMICALS USED IN THE TREATMENT OF DEPRESSION: A REVIEW - APOORVA HA; SEEMA MEHDI; KRISHNA KL; NABEEL K (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Depression is a condition of no mood and loss of interest in any activity that can diminish a person’s thinking, conduct, tendencies, emotional state, and a sense of well-being. Although there is a conventional class of medication which have been beneficial in the treatment of depression, current studies have reported having side effects which can be minimized by the intervention of herbs and phytochemicals. Most of the studies have proven the various mechanisms and have started to research a very ground-breaking method by glancing the ancient treatmen. Where this new approach of using the herbs and phytochemicals has shown better results alone and in combination with conventional drugs which has shown lesser adverse effects. The practice of phytomedicine is an additional option for the treatment of depression. In the various segments of treating the depression, the mainstream can be a breakthrough including phytoconstituents. In this aspect, there are many contributions for the treatment of the depression acting to the neuronal level signaling and the phytoconstituents also have shown some basic mechanisms in the treatment of depression as that of the conventional medications following some primary hypothesis and signaling pathways and life interactions that effects the brain in either way to treat the depression in all sort of way. Clinical evidence is required to provide backing to the safety and effectiveness of herbs and phytochemicals alone or in combination with currently available drugs to overcome the reported side effects during the treatment of depression.